Analysis Of The Influence Of Digitality Aspects On Employee Performancein The Field Of Hospitality In Gianyar Regency, Bali - I Made Darsana; Nyoman Surya Wijaya (Institute of Computer Science (IOCS), 2022)
The rise of employee layoffs is one of the impacts of the COVID-19 pandemic. This happens in all business fields, including hospitality. Hotel business managers must be able to adapt to this situation, one of which is by applying a relevant HR management model to be applied in the digitalization era. Based on this review, it aims to analyze the influence of digitalization aspects (digital leadership, digital collaboration, digital skills) on employee performance in the hospitality sector in Gianyar Bali Regency. This research is a quantitative study with data collection techniques through questionnaires distributed to 100 hotel employees in Gianyar Bali Regency. The results of the study conclude that employee performance is influenced by aspects of digitalization consisting of digital leadership, digital collaboration, and digital skills. Digital skills are also influenced by digital leadership, but not by digital collaboration. This research can be a recommendation for the government and hotel managers in compiling a relevant human resource management model to be applied in the new normal era.